Effects of Metacognitive Reading Strategy Training on Undergraduates' reading comprehension - Nadine, William Norman (Universiti Malaysia Sarawak, (UNIMAS), 2005)
This study aims to examine the effects of metacognitive training on undergraduates' reading comprehension through the administration of the self- questioning strategy. There were sixty-one respondents assigned randomly to participate in this study comprising first-year University Malaysia of Sarawak's (UNIMAS) undergraduates from the Human Resource Development Programme under the Faculty of Cognitive Sciences and Human Development.. Respondents were assigned randomly to the experimental group (EG) and control group (CG). This study involves the pretest, metacognitive training, and posttest sessions. The metacognitive training was only administered to the EG respondents. Both experimental and control groups were given the pretest and posttest tests. The EG respondents TeachQucst training were given training on self-questioning strategy based on the model that was integrated with the Know/Want to know/Learnt (KWL) strategy. There is a significant difference in the scores obtained by those who receive metacognitive training on self-questioning and those who did not. Therefore, the null hypothesis is rejected. The questions generated by the respondents at the pre-test and post-test sessions were analysed. Most of the EG respondents did not generate divergent and evaluative thinking questions at the pretest and posttest sessions. However. there is a slight increase in the number of respondents who generated at least one question of divergent and evaluative thinking questions at the posttest session. Most of the CG respondents did not generate convergent, divergent and evaluative thinking questions at both sessions. Therefore. metacognitive training could assist students in improving their reading comprehension.